The Role of Bank Mega's Strategic Management in Facing the 2023 Global Economic Recession - Dewi Novitasari (Clean and Sustainable Production, 2023)
This research aims to analyze the role of strategic management in facing the 2023 global economic recession at Bank Mega. The global economic recession that will occur in 2023 will have a significant impact on the banking sector, including Bank Mega. Strategic Management has an important role in managing the negative impact of this recession and ensuring the strategic continuity of the bank. Some of the strategic steps taken by strategic management include increasing strategic efficiency, better risk management, diversifying products and services, developing new marketing strategies, and increasing the use of information technology. Apart from that, collaboration with external parties such as international financial institutions and regulators is also carried out to obtain advice and assistance in dealing with a recession